PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE TERHADAP PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS IX SMP NEGERI 11 PADANG - SILVIA SILVIA (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts is one of the most important mathematical goals for students to master the material and prerequisites for the next concept, in fact in class IX SMP Negeri 11 Padang student's understanding of mathematical concepts is still low, so it needs to be improved and the one of the objectives of mathematics learning can be reached. The teacher dominates the learning carried out. The effort to solve this problem is by applying a learning model that can facilitate students to understand the material with their own knowledge. The learning model that can be used is a cooperative learning model type Think Pair Square (TPSq). The type of this research is quasi-experimental with a research design namely Static Group Design. Based on the results of data analysis using the t-test, obtained P-value = 0.012 ˂ α = 0.05, the conclusion is the student’s understanding of the mathematics concept who learn with the cooperative learning type TPSq model better than students using conventional learning. Keywords— cooperative learning, Think Pair Square, mathematical concepts, conventional learning